1972
DOI: 10.1111/j.1471-4159.1972.tb06220.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Distribution of Pyruvate Kinase (Ec 2.7.1.40) in Cerebral Cortex

Abstract: —The subcellular distribution of pyruvate kinase (EC 2.7.1.40) in the cerebral cortex of the rat was studied. The enzyme, which had been previously reported in the cytoplasm, was found to be present in synaptosomal, microsomal and mitochondrial fractions as well. The activity of the enzyme in the synaptosomal fraction was localized predominantly in the synaptosomal membrane and was not dissociated by repeated washing or recentri‐fuging in a sucrose gradient. Some kinetic parameters of the membrane‐associated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…MI PK localization was found by histoenzymology, immunocytoenzymology , and immunofluorescence to be essentially cytoplasmic in the central and in the peripheral nervous system, in situ as well as in vitro. These results are consistent with previous subcellular fractionation studies of PK: MI PK was observed in rat synaptosomal mitochondrial, microsomal, and soluble fractions of rat brain (Tamir et al, 1972). However, these biochemical findings were criticized, for they might have been caused by electrostatic binding of PK to particles (Knull, 1977).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…MI PK localization was found by histoenzymology, immunocytoenzymology , and immunofluorescence to be essentially cytoplasmic in the central and in the peripheral nervous system, in situ as well as in vitro. These results are consistent with previous subcellular fractionation studies of PK: MI PK was observed in rat synaptosomal mitochondrial, microsomal, and soluble fractions of rat brain (Tamir et al, 1972). However, these biochemical findings were criticized, for they might have been caused by electrostatic binding of PK to particles (Knull, 1977).…”
Section: Discussionsupporting
confidence: 91%
“…It must be added that the high intensity of staining of cerebellar glomeruli could be related to the number of synapses included in these structures. As a matter of fact, M, PK was found to be abundant in synaptosomes (Tamir et al, 1972). Cell identification in situ as well as in vitro has been performed on morphological criteria with the exception of the demonstration of the presence of GFAP in glial cell cultures.…”
Section: Figs 11-12 (11)mentioning
confidence: 99%
“…Fractions were analyzed for enzyme activity and protein concentration. Enzyme activities were determined at 30 "C using previously reported assays: aldolase (Bergmeyer et al, 1974), GAPDH (Bergmeyer et al, 1974), PK (Tamir et al, 1972), and LDHM (Stolzenbach, 1966).…”
Section: Affinity Chromatographymentioning
confidence: 99%
“…Hexokinase is found associated with mitochondria (Johnson, 1960;Craven et al, 1969). Aldolase Masters, 1972, 1975;Knull, 1978), pyruvate kinase (Tamir et al, 1972;Knull, 1977Knull, , 1978, lactate dehydrogenase (Berlet and Lehnert, 1978;Knull, 1978), and phosphofructokinase and glyceraldehyde-phosphate dehydrogenase (Knull, 1978) have also been isolated in membranes containing subcellular fractions. The nature of the interactions between many of these enzymes and the membrane fractions appears to be electrostatic since an increase in the ionic strength of the suspension buffer releases the particle-bound enzymes Masters, 1972, 1973;Knull, 1978).…”
Section: Interaction Of Selected Brain Glycolytic Enzymes With Anmentioning
confidence: 99%